Recruit for Indian. Contribution of the Kingdom of Galicia to the Imperial Defense (1702) - Lago Almeida, Héctor (Cuadernos de Historia Moderna, 2015)
The object of this research is constituted by the two military units of 2,000 men created in the Kingdom of Galicia in 1702. It was a service for the crown that aimed to defend the Empire –at first in Flanders and then in America– in a moment when the military and political disturbances that would trigger the War of Spanish Succession began to emerge. Given the context of transition lived by the monarchy, we will immerse ourselves in the study of the process of creation of these two tercios: from the negotiations between Philip V and the representative institution of the kingdom for their granting, to the actual execution of the recruitment and the sociological characterization of individuals who were forced to serve as soldiers from the tudense case.
Keywords: Recruitment; troops; soldiers; War of Spanish Succession; Philip V; tercios; America; Juntas del Reino de Galicia; Galicia; Tui; local authorities.